Images of the futures in a 10-year perspective of immigrant families moved from Russia to European countries after the beginning of the full-scale invasion of Ukraine on 24.02.2022 : In seeking “the city which is to come” - Melnikov, Andrey (My University, 2025)
Since the beginning of the war in Ukraine in 2022, up to 800,000 Russian citizens have left their country. This migration wave has a specificity compared to previous ones. Migrants are more educated, wealthier, with anti-war, anti-regime positions, and political motives for emigration rather than economic. This wave also differentiates internally. Generally, migrants in European countries experience more stability compared to the South Caucasian and Central Asian regions, where precariousness of living triggers a drastic decrease in the capacity for long-term planning. The families in this research settled in Finland, the Netherlands, Hungary, Croatia, and Great Britain, which reflected in their futures images and the envisioning process. This research is an intersectional. The focus is on the images of the future under a specific angle: the futures of migrant families. How do Russian migrant families of the last wave anticipate and envision their futures in given European societies? Considering futures studies, this research aims to fill a gap between studies of individual and societal images of the futures since the family is a micro-social unit of individuals who are doing family (Dermott & Fowler 2020), including “doing” foresight. Hence, the personal and family future images are under integrative analysis. The futures images were explored theoretically and empirically through contextual and structural frames. Additionally, families' experience of foresight practice was analyzed. The theoretical part contains a critical review of the contemporary research and conceptual analysis of the prominent ideas, including Polak’s (1973), Bell and Mau’s (1971), and Rubin’s (2000), as well as theoretical grounds for the analysis of foresight activities (Minkkinen et al. 2019). The basic content-structural scheme of the image of the future was suggested. A mixed method was adopted for the deeper empirical exploration. Initial data was collected by semi-structured in-depth group interviews of the families, scaffolded by the PESTEC(V) framework. The modified Kinetic Family Drawing method and unstructured observation were incorporated into the interviewing. Data was analyzed through Causal Layered Analysis and Thematic analysis that also contained “six foresight frames”. Through theoretical analysis core elements and origin of the image of the future were distilled. The coherent texts of four future images of the families were composed, namely, “A Man Called Ove” in “Tomorrowland”: “Healthy human socialist” Utopia; “Hobbit[s]” in the “Naked Harbor”: Inter-topia; “Blade Runner[s 2035]” in the “Westworld”: Dystopia; “The Road”: Apocalypse. The results of the empirical investigation primarily support theoretical assumptions and previous studies in the field. The core of the family future images contains strong, optimistic beliefs akin to faith. The reconstructed composition of the futures images inherits cultural civilizational patterns – a utopia-eschatology-dystopia’s carcass. Generally, the image of the future is heterogeneous. It contains overlapped elements of all foresight outcomes, but the scenario remarkably prevails, specifically the optimistic ones. The findings provide evidence that the family has its inner specificity in foresight practice: the members’ leading-passive roles, the implicit power of beliefs, and the optimism-pessimism balance. The cultural identity impact is also evident. This research argues for a multidisciplinary and intersectional character of the following investigations of such a complex phenomenon. Cultural, psychological, educational, and philosophic aspects might be considered first, also concerning family and migration studies. However, to maintain the specificity, i.e., futuristic aspect and holistic approach, the umbrella of futures studies is preferable. The main conclusion to be drawn from this work is that these families might primarily be considered an asset for receiving societies, at least, in the sense of internal family aspirations, their agency, and values towards a safe and prosperous future that, in the best scenario, might contribute to a peaceful and prosperous host society.
Keywords: images of the future, migrant family, Causal Layered Analysis, foresight, Russian migrants